Exploring the role of mindfulness on obligatory exercise among young athletes: mediating roles of obsessive passion and cognitive state anxiety - Li, Qianyuan; Li, Li; He, Qianqian; Wang, Huilin (Frontiers in Public Health, 2024)
Introduction In the current trend toward youthfulness and age reduction in competitive sports, the issue of obligatory exercise among young athletes is becoming more severe. This not only affects their physical and mental health but also hampers their future prospects in the sports world. While delving into the impact of mindfulness on the issue of obligatory exercise among young athletes, it reveals the mediating role of obsessive passion and cognitive state anxiety. Methods This study is a cross-sectional research that employs convenience and snowball sampling methods. We selected 403 young athletes from several universities and high-level sports teams in the central-southern region of China as valid samples and used AMOS v.23 to construct a structural equation model to validate the hypotheses. Results The research findings indicate a significant positive correlation between obsessive passion, cognitive state anxiety, and obligatory exercise. Furthermore, obsessive passion and cognitive state anxiety mediate the relationship between mindfulness and obligatory exercise. This implies that young athletes can better regulate their emotional state during training, manage training loads sensibly, and avoid issues with obligatory exercise through mindfulness training. Discussion In conclusion, to enhance the cognitive levels of young athletes and reduce their obligatory exercise behaviors, national sports authorities and coaching teams should develop reasonable mindfulness training programs for athletes and encourage their participation in mindfulness training.